Analisis Program Keluarga Harapan (PKH) Dalam Upaya Penanggulangan Kemiskinan - Nuraulia, Ridela; Purbaningrum, Dini Gandini; Nurhadi, Salma Putri (As-Syirkah: Islamic Economic & Financial Journal, 2023)
The Family Hope Program (PKH) is a government policy program that seeks to eradicate poverty. This program is distributed from cities and villages throughout Indonesia. By looking at this PKH policy can reduce poverty. This article aims to see how far the program plays a role in reducing poverty. This research uses descriptive qualitative method. The results of this study indicate that the program has been running smoothly, marked by socialization, program supervision, and program implementation which is carried out regularly. Keywords: Poverty, Policy Analysis, Family Hope Program